Differential self-reported COVID-19 impacts among U.S. secondary teachers by race/ethnicity - McCauley, Erin Josephine; Cooperstock, Alexandra (Frontiers in Education, 2022)
The COVID-19 pandemic created drastic changes for public education in the United States, including the role and responsibilities of educators. This study explores the self-reported psycho-social implications of COVID-19 among U.S. secondary teachers who are white, Black, Indigenous, and people of color. Using a national survey (n=1,478) fielded between October 2020 and March 2021, we capture teachers’ self-reported level of concern, life change, impact on thinking, and impact on teaching ability due to the COVID-19 pandemic. While teachers who are Black, Indigenous, and people of color report higher levels of concern and daily life change stemming from COVID-19, they report lower impacts on their teaching ability relative to their white peers. These findings are consistent with racial/ethnic disparities in COVID-19 case rates and mortality and highlight the resiliency of the U.S. secondary teachers who are Black, Indigenous, and people of color.